OPTIMIZING THE USE OF ROCK ASH AS FINE AGGREGATES WITH THE ADDITION OF ADDITIVES TO THE CONCRETE MIXTURE WITH A COMPRESSIVE STRENGTH OF 350 Kg/cm2 - Triaswati; Srie Subekti; Sulchan Arifin; Febri Aditya (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
Stone dust nowadays is a side product of the stone crushing industry, the quality of which is quite a lot that it becomes a waste that needs to be handled. This study is intended to find out the composition of stone dust by adding some additive substance type D and type F to reach a compressive strength of 350 kg/cm2. The variation of percentage of stone dust on the composition of concrete mixture is 0%, 20%, 40%, 60%, 80%, 100%. The design of concrete mixture composition refers to the procedure of making preparation of the normal concrete mixture. SNI 03-2384-1993. The size of the cylinder test object is 15 cm in diameter and 30 cm in height. The result of this research shows that the mixture using stone dust has quite an effect on the compressive strength of concrete. From the result of the experiment, it is shown that for compressive strength of 350 kg/cm2, we can use 100% of stone dust with a resulted compressive strength of 445 kg/cm2.